1991
DOI: 10.1111/j.1151-2916.1991.tb06940.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Etching of α‐Sialon Ceramics

Abstract: Plasma etching of j?-Si3N4, cy-sialon/j?-Si3N4 and a-sialon ceramics were performed with hydrogen glow plasma at 600°C for 10h. The preferential etching of j?-Si3N4 grains was observed. The etching rate of cy-sialon grains and of the grain-boundary glassy phase was distinctly lower than that of B-Si3N4 grains. The size, shape, and distribution of BSi3N4 grains in the a-sialon/&Si3N4 composite ceramics were revealed by the present method. [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…. Plasma etching could improve the quality of the SEM image because of the preferential etching of β‐Si 3 N 4 grains 47 . The volumetric ratio of the secondary phases to Si 3 N 4 was 13%, evaluated by the attached grid on the top of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…. Plasma etching could improve the quality of the SEM image because of the preferential etching of β‐Si 3 N 4 grains 47 . The volumetric ratio of the secondary phases to Si 3 N 4 was 13%, evaluated by the attached grid on the top of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(b) also indicates that the etching rate of Si-C-N is faster than that of the SiC filler particles. Mitomo et al 23 compared the etching speed of a-SiAlON, b-Si 3 N 4 , and grain boundary phase (Y 2 O 3 1AlN), and reported that the etching rate of b-Si 3 N 4 was higher than that of the other phases. They reported that this may be because of the higher reactivity of a single compound than the more complex compounds with the activated etching gas.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(b) also indicates that the etching rate of Si–C–N is faster than that of the SiC filler particles. Mitomo et al 23 . compared the etching speed of α‐SiAlON, β‐Si 3 N 4 , and grain boundary phase (Y 2 O 3 +AlN), and reported that the etching rate of β‐Si 3 N 4 was higher than that of the other phases.…”
Section: Resultsmentioning
confidence: 99%
“…In this contribution the possibility of a surface structuring method by plasma-etching is presented. For this kind of structuring the α/βsialon ratio has a great influence on the surface topography because of the different etching-rate of αand β-sialon [3].…”
Section: Introductionmentioning
confidence: 99%